Antioxidant Constituents of Cotoneaster melanocarpus Lodd. - Adelheid H. Brantner; Javzan Batkhuu; Agnieszka D. Lower-Nedza; Myagmar Nandintsetseg; Veronika M. D. Holzer (MDPI AG, 2013)
The aim of this study was the evaluation of the antioxidant capacity of Cotoneaster melanocarpus Lodd. and the identification of antioxidant active constituents of this plant. C. melanocarpus Lodd. is a shrub indigenous to Mongolia and used in Traditional Mongolian Medicine as a styptic. Before extraction, the plant material was separated into three parts: young sterile shoots, older stems and leaves. All these parts were extracted with water, methanol, ethyl acetate, dichloromethane and hexane, successively. The methanolic extract of the sterile shoots showed the highest antioxidant activity in the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay (IC50 30.91 ± 2.97 µg/mL). This active extract was further analyzed with chromatographic methods. TLC fingerprinting and HPLC indicated the presence of the flavonol glycosides quercetin-3-O-rutinoside (rutin), quercetin-3-O-galactoside (hyperoside) and quercetin-3-O-glucoside (isoquercetin), ursolic acid as well as chlorogenic acid, neochlorogenic acid and cryptochlorogenic acid. The findings were substantiated with LC-MS. All identified compounds have antioxidant properties and therefore contribute to the radical scavenging activity of the whole plant.